Responding to future regime shifts with agrobiodiversity: A multi-level perspective on small-scale farming in Uganda - Kozicka, Marta; Gotor, Elisabetta; Ocimati, Walter; Jager, Tamar de; Kikulwe, Enoch Mutebi; Groot, Jeroen C.J. (Elsevier, 2020)
We analyse the impact of two large-scale regime shifts caused by disease incidence or climate change, and associated crop productivity and price changes, on banana-based smallholders in Uganda. We evaluate these farmers' vulnerability and assess the potential of using increased crop diversity to improve their resilience. We further explore trade-offs and synergies between environmental, economic and nutritional outcomes faced by the farmers in their decision making when a regime shift occurs. We simulate the large-scale scenarios with the IMPACT model and use the results obtained to assess their effect at the local level using the bio-economic farm-household model, FarmDESIGN.